Answer:
x = -4, y = 7, z = 2.
Step-by-step explanation:
4x + 2y + 5z = 8......(1)
5x + 3y + 4z = 9......(2)
6x + 3y + 3z = 3......(3)
Subtract: equation (2) - equation (3):
-x + z = 6 ........(4)
Multiply (1) by 3 and (2) by 2:
12x + 6y + 15z = 24 .........(5)
10x + 6y + 8z = 18 ...........(6)
Subtract: (5) - (6):
2x + 7z = 6..............(7)
Multiply equation (4) by 2:
- 2x + 2z = 12.........(8)
Add (7) + (8):
9z = 18 , so z = 2.
Substitute for z in equation (4)
-x + 2 = 6
-x = 4 so x = -4.
Now find y by substituting in equation (1):
4(-4) + 2y + 5(2) = 8
2y = 8 + 16 - 10 = 14
y = 7.